The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00590-013-1307-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute quadriceps tendon rupture: a pragmatic approach to diagnostic imaging

Abstract: We propose that all patients who have a suspected quadriceps tendon rupture after clinical examination and radiography should either proceed directly to magnetic resonance imaging or be initially assessed by ultrasound, and in those with positive findings, a supplementary magnetic resonance imaging to eliminate false positive diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
17
0
6
Order By: Relevance
“…MR imaging has been shown to be of higher specificity than ultrasonography for determining whether the quadriceps tear is complete or partial, and thus MR imaging is important for presurgical planning. 16,22 MR imaging findings of complete quadriceps rupture show fluid signal within a torn and retracted quadriceps tendon; no fibers are identified inserting on the patella. The quadriceps stump retracts cranially and the patella retracts caudally, often associated with a wavy appearance of the patellar tendon.…”
Section: Quadriceps Injury Quadriceps Rupture and Partial Tearmentioning
confidence: 97%
See 1 more Smart Citation
“…MR imaging has been shown to be of higher specificity than ultrasonography for determining whether the quadriceps tear is complete or partial, and thus MR imaging is important for presurgical planning. 16,22 MR imaging findings of complete quadriceps rupture show fluid signal within a torn and retracted quadriceps tendon; no fibers are identified inserting on the patella. The quadriceps stump retracts cranially and the patella retracts caudally, often associated with a wavy appearance of the patellar tendon.…”
Section: Quadriceps Injury Quadriceps Rupture and Partial Tearmentioning
confidence: 97%
“…Rupture occurs most frequently in men more than 40 years of age, and is also associated with underlying systemic disease or medications, such as renal failure, diabetes, gout, hyperparathyroidism, rheumatoid arthritis, systemic lupus erythematosus, obesity, and steroid and fluoroquinolone use. [16][17][18][19][20][21] Bilateral spontaneous ruptures have been reported in patients with gout, diabetes, and steroid use. 20 Ruptures occur most frequently at the insertion of the quadriceps on the patella.…”
Section: Quadriceps Injury Quadriceps Rupture and Partial Tearmentioning
confidence: 99%
“…Perfitt et al reported that 67% of patients were misdiagnosed at their initial presentation [33]. The enlarged soft tissue envelope in obese patients can obscure the suprapatellar gap and make the diagnosis of QTR more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has the advantages of being cheaper and easier to get compared to MRI; however, it is operator dependent and the diagnosis can be missed if performed by an inexperienced sonographer [20, 39]. MRI remains the modality of choice, as Perfitt et al showed in his study that it has a 100% sensitivity and specificity with a positive predictive value of 100 in detecting a quadriceps tendon rupture compared to US [33, 35, 39], but increased cost and limited availability of MRI in the emergency setting are major limitations [20, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…Perfitt og félagar lýstu því að naemi ómskoðunar vaeri 100% en sértaekið aðeins 67%. 9 Til að forðast óþarfa meðferð þarf að hafa þetta í huga áður en óm-skoðun er pöntuð og við túlkun á niðurstöðunum ef hún er framkvaemd. Ein lausn gaeti verið að framkvaema segulómskoðun en naemi og sértaeki hennar var 100% í fyrrgreindri rannsókn.…”
Section: Mynd 2 Röntgenmynd Sem Sýnir Vinstra Hné Sjúklingsins Eftirunclassified